Perspektif Hukum Islam Terhadap Duwi Papendre’ dalam Pernikahan Adat Bugis - Mawardi Mawardi (Jurnal Multidisiplin Ibrahimy, 2025)
Indonesia is a vast country with diverse customs and cultures across its regions. It is critical to protect and promote these customs and cultures. Our ancestors' customs and traditions, rich in values and meaning, define human behaviour in society and serve as guidelines for living a dignified life. For example, the Bugis of Nipah Panjang 1 Village, Nipah Panjang District, Tanjung Jabung Timur Regency, Jambi Province, continue to practise a wedding tradition known as duwi papendre’. Duwi papendre’ is one of the basic requirements that the prospective husband's family must meet during a traditional wedding. Before proposing to a Bugis girl in Nipah Panjang, a man must perform duwi papendre’. This study focuses on the practice of duwi papendre' in Nipah Panjang Village, as well as the impact of Islamic law on Bugis traditional marriage. This study used a qualitative research method. This study used the following data sources: Primary data, including data obtained from field research objects through interviews and observations with relevant parties such as community leaders, the Religious Affairs Office (KUA), Duwi Papendre' practitioners, and other community members about the Duwi Papendre' practice implemented in the Nipah Panjang 1 Village community. Secondary data, or supporting or complementary data related to the research problem, were gathered from various sources, including the Quran, Hadith, journal articles, theses, etc. According to the findings of this study, the Duwi Papendre’ practice involves the groom paying a sum of money to the family of the woman he wishes to marry. This Duwi Papendre' is not a dowry but funds for organising a wedding reception or walimatul 'ursy at the woman's home. In contrast, the dowry must be given to the bride as her personal property. The amount of duwi papendre’ to be given is determined by both parties' agreement, which typically considers the prospective bride's social, educational, and economic status and the prospective groom's abilities. According to Islamic law, duwi papendre' in the Nipah Panjang 1 area is permissible as long as there is no burden or coercion and it is based on voluntary and mutual agreement. The practice of duwi papendre' is acceptable in Islam, because a custom or 'urf can be made law if it is widely accepted and there is no evidence to the contrary. Sharia recommends giving duwi papendre’ in a marriage proposal to strengthen the relationship between the two parties. Similarly, the obligation to give duwi papendre' is to organise a wedding reception or walimatul 'ursy, which is a recommended act in sharia as long as it is carried out without elements that contradict sharia and aims to follow the Prophet Muhammad's sunnah.